2010
DOI: 10.1177/0047287509355323
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Health Risk Perception Among Low-risk-taking Tourists Traveling to Developing Countries

Abstract: This article focuses on tourists' perception of health risk among tourists who intend to travel to developing countries. It examines the relative importance tourists assign to this risk. It unveils the factors that shape health risk perceptions and explores the relative role of each factor in shaping tourists' perception. With a sample of 232 and a self-administered questionnaire, the study interviewed visitors at a travelers medical clinic before their trip. Using ordered logistic regression, the results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
155
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(164 citation statements)
references
References 63 publications
4
155
1
4
Order By: Relevance
“…The study also found that different demographic groups differ in their risk perception. The findings were consistent with the previous studies (Jonas, et al 2011;Kozak, et al 2007;Rittichainuwat & Chakraborty, 2009;Sonmez & Graefe, 1998) mentioned that tourists are more likely to choose safe destinations.…”
Section: Conclusion Implications and Limitationssupporting
confidence: 93%
“…The study also found that different demographic groups differ in their risk perception. The findings were consistent with the previous studies (Jonas, et al 2011;Kozak, et al 2007;Rittichainuwat & Chakraborty, 2009;Sonmez & Graefe, 1998) mentioned that tourists are more likely to choose safe destinations.…”
Section: Conclusion Implications and Limitationssupporting
confidence: 93%
“…In addition, tourists may use a number of risk reduction strategies such as conducting additional research to reduce uncertainty of the situation (Reichel, Fuchs, & Uriely, 2009). Furthermore, perception of control over the risk influences an individual's willingness to travel (Jonas, Mansfeld, Paz & Potasman, 2010).…”
Section: Overview Of Literaturementioning
confidence: 99%
“…While previous studies identified these risks as developing during the tourist's vacation, such as the concern of being disconnected from communication (Sheng-Hshiung et al, 1997;Simpson & Siguaw, 2008), or the unavailability of clean water (Eitzinger & Wiedemann, 2007;Jonas et al, 2011), this study indicates these risks develop after the disaster events. This has also been identified in the 2004 Indian Ocean tsunami, where spread of disease due to lack of sanitary water postdisaster was a concern (Watson et al, 2007).…”
Section: Helplessnessmentioning
confidence: 53%
“…The risk perceptions which have been discussed in the tourism literature are summarised in Table 2.2. Similarly, Jonas et al (2011), in their study on health risk perceptions, found that there were nine risk dimensions, ranging from water quality, infection, disease and physical injury, to health impacts of drug use. In terms of crime, risk of assault and theft were the most feared by visitors to South Africa (Richard, 2010).…”
Section: Psychological Riskmentioning
confidence: 99%
See 1 more Smart Citation